"Fideicommissum hereditatis" w źródłach rzymskiego prawa klasycznego - de Bérier, Franciszek Longchamps (Prawo Kanoniczne, 1998)
No formality was required to create afideicommissum hereditatis. Its essence was an order of the deceased that heirs should restore the inheritance or its fraction to a certain person. The order could be written in the last will or in codicilla. In classical Roman law, the fideicommissum was expressed in typical words: peto, rogo, volo, fidei committo, exigo, desidero uti des, cupio des, opto des, credo te daturum, scio, mando, but there was no numerus clausus of the verba fideicommissi. Other writing was also permitted, therefore the will to obligate heirs to the restitution of the inheritance was the essentialium negotii of fideicommissum hereditatis.